Models of necessity - Clark, Timothy; Hicks, Martin G. (Beilstein Journal of Organic Chemistry, 2020)
The way chemists represent chemical structures as two-dimensional sketches made up of atoms and bonds, simplifying the complex three-dimensional molecules comprising nuclei and electrons of the quantum mechanical description, is the everyday language of chemistry. This language uses models, particularly of bonding, that are not contained in the quantum mechanical description of chemical systems, but has been used to derive machine-readable formats for storing and manipulating chemical structures in digital computers. This language is fuzzy and varies from chemist to chemist but has been astonishingly successful and perhaps contributes with its fuzziness to the success of chemistry. It is this creative imagination of chemical structures that has been fundamental to the cognition of chemistry and has allowed thought experiments to take place. Within the everyday language, the model nature of these concepts is not always clear to practicing chemists, so that controversial discussions about the merits of alternative models often arise. However, the extensive use of artificial intelligence (AI) and machine learning (ML) in chemistry, with the aim of being able to make reliable predictions, will require that these models be extended to cover all relevant properties and characteristics of chemical systems. This, in turn, imposes conditions such as completeness, compactness, computational efficiency and non-redundancy on the extensions to the almost universal Lewis and VSEPR bonding models. Thus, AI and ML are likely to be important in rationalizing, extending and standardizing chemical bonding models. This will not affect the everyday language of chemistry but may help to understand the unique basis of chemical language.
Keywords: chemical bonding; chemical ontologies; chemical structure formats; chemical structure representation; chemical structure models; language of chemistry; quantum chemistry

(untitled) - Thompson, B. (Philos. Trans. R. Soc. London, 1798)

(untitled) - Brown, R. (Philos. Mag., 1828)

(untitled) - Einstein, A. (Ann. Phys. (Berlin, Ger.), 1905)

(untitled) - Einstein, A.; Podolsky, B.; Rosen, N. (Phys. Rev., 1935)

(untitled) - Hoffmann, R.; Laszlo, P. (Angew. Chem., Int. Ed. Engl., 1991)

(untitled) - Yoo, C.-S. (Matter Radiat. Extremes, 2020)

(untitled) - Healy, P. (Auslegung, J. Philis., 1986)

(untitled) - Born, M.; Oppenheimer, R. (Ann. Phys. (Berlin, Ger.), 1927)

(untitled) - Bader, R. F. W.; Carroll, M. T.; Cheeseman, J. R.; Chang, C. (J. Am. Chem. Soc., 1987)

Simulation and Similarity: Using Models to Understand the World - Weisberg, M. (Oxford University Press, 2013)

(untitled) - van der Spek, T. M. (Ann. Sci., 2006)

(untitled) - Lewis, G. N. (J. Am. Chem. Soc., 1916)

See for a historical description

Nomenclature of Organic Chemistry - Rigaudy, J.; Klesney, S. P. (IUPAC/Pergamon Press, 1979)

(untitled) - Weininger, D. (J. Chem. Inf. Comput. Sci., 1988)

(untitled) - Heller, S.; McNaught, A.; Stein, S.; Tchekhovskoi, D.; Pletnev, I. (J. Cheminf., 2013)

Valence - Coulson, C. A. (Oxford University Press, 1961)

(untitled) - Mulliken, R. S. (J. Chem. Phys., 1955)

(untitled) - Lennard-Jones, J. E. (Trans. Faraday Soc., 1929)

(untitled) - Boys, S. F.; Bernardi, F. (Mol. Phys., 1970)

(untitled) - Reed, A. E.; Weinstock, R. B.; Weinhold, F. (J. Chem. Phys., 1985)

(untitled) - Horn, P. R.; Mao, Y.; Head-Gordon, M. (Phys. Chem. Chem. Phys., 2016)

Atoms in molecules: a quantum theory - Bader, R. F. W. (Clarendon)
https://global.oup.com/academic/product/atoms-in-molecules-9780198558651

(untitled) - Wick, C. R.; Clark, T. (J. Mol. Model., 2018)

(untitled) - Kermack, W. O.; Robinson, R. (J. Chem. Soc., Trans., 1922)

(untitled) - Walsh, A. D. (J. Chem. Soc., 1953)

Theory of Orientation and Stereoselection - Fukui, K. (Springer, 1975)

(untitled) - Woodward, R. B.; Hoffmann, R. (Angew. Chem., Int. Ed. Engl., 1969)

(untitled) - Mulliken, R. S. (Phys. Rev., 1932)

(untitled) - Díaz–Tinoco, M.; Corzo, H. H.; Pawłowski, F.; Ortiz, J. V. (Mol. Phys., 2019)

Imaging and Manipulating Molecular Orbitals - Mignolet, B.; Kùs, T.; Remacle, F. (Imaging Orbitals by Ionization or Electron Attachment: The Role of Dyson Orbitals, 2013)

(untitled) - Clark, T. (J. Mol. Model., 2017)

Concepts in Computational Spectroscopy: Methods, Experiments and Applications - Grunenberg, J. (Wiley-VCH, 2010)

(untitled) - Murray, J. S.; Politzer, P. (J. Mol. Struct.: THEOCHEM, 1998)

(untitled) - Fiedler, L.; Gao, J.; Truhlar, D. G. (J. Chem. Theory Comput., 2011)

(untitled) - Silva-Junior, M. R.; Schreiber, M.; Sauer, S. P. A.; Thiel, W. (J. Chem. Phys., 2008)

(untitled) - Gasteiger, J.; Marsili, M. (Tetrahedron Lett., 1978)

(untitled) - Gasteiger, J.; Marsili, M. (Tetrahedron, 1980)

(untitled) - Skoraczyński, G.; Dittwald, P.; Miasojedow, B.; Szymkuć, S.; Gajewska, E. P.; Grzybowski, B. A.; Gambin, A. (Sci. Rep., 2017)

Chemical Information - Milne, G. W. A.; Driscoll, J. S.; Marquez, V. E. (Molecular modelling in drug design, 1989)

(untitled) - Watson, J. D.; Crick, F. H. C. (Nature, 1953)

(untitled) - Gillespie, R. J.; Nyholm, R. S. (Q. Rev., Chem. Soc., 1957)

(untitled) - Green, J. C.; Green, M. L. H.; Parkin, G. (Chem. Commun., 2012)

(untitled) - Engkvist, O.; Norrby, P.-O.; Selmi, N.; Lam, Y.-h.; Peng, Z.; Sherer, E. C.; Amberg, W.; Erhard, T.; Smyth, L. A. (Drug Discovery Today, 2018)

(untitled) - Gromski, P. S.; Granda, J. M.; Cronin, L. (Trends Chem., 2020)

(untitled) - Steiner, S.; Wolf, J.; Glatzel, S.; Andreou, A.; Granda, J. M.; Keenan, G.; Hinkley, T.; Aragon-Camarasa, G.; Kitson, P. J.; Angelone, D.; Cronin, L. (Science, 2019)

(untitled) - Roch, L. M.; Häse, F.; Kreisbeck, C.; Tamayo-Mendoza, T.; Yunker, L. P. E.; Hein, J. E.; Aspuru-Guzik, A. (PLoS One, 2020)

(untitled) - Bédard, A.-C.; Adamo, A.; Aroh, K. C.; Russell, M. G.; Bedermann, A. A.; Torosian, J.; Yue, B.; Jensen, K. F.; Jamison, T. F. (Science, 2018)

The Fourth Paradigm: Data-Intensive Scientific Discovery - Hey, T.; Tansley, S.; Tolle, K. (2009)

(untitled) - Corey, E. J.; Wipke, W. T. (Science, 1969)

(untitled) - Gelernter, H. L.; Sanders, A. F.; Larsen, D. L.; Agarwal, K. K.; Boivie, R. H.; Spritzer, G. A.; Searleman, J. E. (Science, 1977)

(untitled) - Gelernter, H.; Rose, J. R.; Chen, C. (J. Chem. Inf. Comput. Sci., 1990)

(untitled) - Segler, M. H. S.; Preuss, M.; Waller, M. P. (Nature, 2018)

(untitled) - Coley, C. W.; Barzilay, R.; Jaakkola, T. S.; Green, W. H.; Jensen, K. F. (ACS Cent. Sci., 2017)

(untitled) - Kayala, M. A.; Baldi, P. (J. Chem. Inf. Model., 2012)

(untitled) - Klucznik, T.; Mikulak-Klucznik, B.; McCormack, M. P.; Lima, H.; Szymkuć, S.; Bhowmick, M.; Molga, K.; Zhou, Y.; Rickershauser, L.; Gajewska, E. P.; Toutchkine, A.; Dittwald, P.; et al. (Chem, 2018)

(untitled) - Hammett, L. P. (J. Am. Chem. Soc., 1937)

(untitled) - Beck, B.; Horn, A.; Carpenter, J. E.; Clark, T. (J. Chem. Inf. Comput. Sci., 1998)

Chemical Data Analysis in the Large: The Challenge of the Automation Age, Beilstein Bozen Symposium 2000, 22 – 26 May 2000, Bolzano, Italy

(untitled) - Brown, N.; Ertl, P.; Lewis, R.; Luksch, T.; Reker, D.; Schneider, N. (J. Comput.-Aided Mol. Des., 2020)

(untitled) - Hansch, C.; Fujita, T. (J. Am. Chem. Soc., 1964)

(untitled) - Free, S. M., Jr; Wilson, J. W. (J. Med. Chem., 1964)

Cybernetics and forecasting techniques - Ivakhnenko, A. G.; Lapa, V. G. (American Elsevier Pub. Co., 1967)

Neural Networks in Chemistry and Drug Design: An Introduction - Zupan, J.; Gasteiger, J. (Wiley-VCH, 1999)

(untitled) - Ma, J.; Sheridan, R. P.; Liaw, A.; Dahl, G. E.; Svetnik, V. (J. Chem. Inf. Model., 2015)

(untitled) - Elrod, D. W.; Maggiora, G. M.; Trenary, R. G. (J. Chem. Inf. Comput. Sci., 1990)

(untitled) - Bersohn, M.; Esack, A. (Chem. Rev., 1976)

(untitled) - Toropov, A. A.; Toropova, A. P.; Benfenati, E. (Eur. J. Med. Chem., 2010)

(untitled) - Durant, J. L.; Leland, B. A.; Henry, D. R.; Nourse, J. G. (J. Chem. Inf. Comput. Sci., 2002)

Roald Hoffmann on the Philosophy, Art, and Science of Chemistry - Grosholz, E. R.; Hoffmann, R. (Oxford University Press, 2014)

Molecular Structure: Understanding Steric and Electronic Effects from Molecular Mechanics - Allinger, N. L. (John Wiley & Sons, 2010)

(untitled) - Ibrahim, P.; Clark, T. (Curr. Opin. Struct. Biol., 2019)

The Structure of Scientific Revolutions - Kuhn, T. S. (University of Chicago Press, 1970)

Modeling Theory in Science Education - Halloun, I. (Kluwer Academic Publishers, 2004)

(untitled) - Wendel, P. J. (Sci. Educ., 2008)

Chemist's Guide to Valence Bond Theory - Shaik, S. S.; Hiberty, P. A. (John Wiley & Sons, 2007)

(untitled) - Hoffmann, R.; Shaik, S.; Hiberty, P. C. (Acc. Chem. Res., 2003)

(untitled) - Dewar, M. J. S. (Angew. Chem., Int. Ed. Engl., 1971)

(untitled) - Zimmerman, H. E. (Acc. Chem. Res., 1971)

(untitled) - Thirman, J.; Engelage, E.; Huber, S. M.; Head-Gordon, M. (Phys. Chem. Chem. Phys., 2018)

(untitled) - Clark, T.; Heßelmann, A. (Phys. Chem. Chem. Phys., 2018)

(untitled) - Bader, R. F. W. (Found. Chem., 2011)

(untitled) - Extance, A. (Chem. World, 2017)
https://www.chemistryworld.com/news/do-hydrogen-bonds-have-covalent-character/2500428.article.

(untitled) - Rooks, E. (Chem. World, 2018)
https://www.chemistryworld.com/news/when-it-comes-to-halogen-bonds-electrostatics-arent-the-hole-story/3008474.article.

(untitled) - Hermans, J. (Adv. Protein Chem., 2005)

(untitled) - Jorgensen, W. L.; Schyman, P. (J. Chem. Theory Comput., 2012)

(untitled) - Bauzá, A.; Mooibroek, T. J.; Frontera, A. (Angew. Chem., Int. Ed., 2013)

(untitled) - Trubenstein, H. J.; Moaven, S.; Vega, M.; Unruh, D. K.; Cozzolino, A. F. (New J. Chem., 2019)

(untitled) - Wang, W.; Ji, B.; Zhang, Y. (J. Phys. Chem. A, 2009)

(untitled) - Politzer, P.; Murray, J. S.; Clark, T. (Phys. Chem. Chem. Phys., 2013)

(untitled) - Thomas, H. B.; Hennemann, M.; Kibies, P.; Hoffgaard, F.; Güssregen, S.; Hessler, G.; Kast, S. M.; Clark, T. (J. Chem. Inf. Model., 2017)

(untitled) - Schürer, G.; Gedeck, P.; Gottschalk, M.; Clark, T. (Int. J. Quantum Chem., 1999)

(untitled) - Politzer, P.; Murray, J. S.; Concha, M. C. (J. Mol. Model., 2008)

(untitled) - Thakkar, A. J. (AIP Conf. Proc., 2012)

(untitled) - Politzer, P.; Murray, J. S.; Clark, T. (J. Phys. Chem. A, 2019)

(untitled) - Hoffmann, R.; Minkin, V. I.; Carpenter, B. K. (Bull. Soc. Chim. Fr., 1996)

(untitled) - Politzer, P.; Murray, J. S. (J. Mol. Model., 2018)

(untitled) - Modarresi, H.; Dearden, J. C.; Modarress, H. (J. Chem. Inf. Model., 2006)

(untitled) - Saleh, N.; Ibrahim, P.; Saladino, G.; Gervasio, F. L.; Clark, T. (J. Chem. Inf. Model., 2017)

(untitled) - Clark, T.; Hennemann, M.; Murray, J. S.; Politzer, P. (J. Mol. Model., 2007)

(untitled) - Clark, T. (Faraday Discuss., 2017)

(untitled) - Arunan, E.; Desiraju, G. R.; Klein, R. A.; Sadlej, J.; Scheiner, S.; Alkorta, I.; Clary, D. C.; Crabtree, R. H.; Dannenberg, J. J.; Hobza, P.; Kjaergaard, H. G.; Legon, A. C.; et al. (Pure Appl. Chem., 2011)

Common Patterns in Revolutionary Infrastructures and Data - Wittenburg, P.; Strawn, G. (2018)